2018
DOI: 10.1021/acs.molpharmaceut.7b01128
|View full text |Cite
|
Sign up to set email alerts
|

Photodisruption of the Structurally Conserved Cys-Cys-Trp Triads Leads to Reduction-Resistant Scrambled Intrachain Disulfides in an IgG1 Monoclonal Antibody

Abstract: Photostability conditions as prescribed by ICH guidelines induced highly reduction-resistant scrambled disulfides that contribute to the population of apparent nonreducible aggregates in an IgG1 mAb. Photoinduced cross-linked species were isolated under reducing conditions using an organic phase size exclusion chromatography (OP-SEC) method, followed by O-labeling tryptic mapping to identify cross-linked peptides. Disulfide scrambling was observed within the IgG1 structurally conserved-intrachain cysteine-cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…The fact that these crosslinks (which primarily form for mAb 1) are nonreducible suggests mechanisms other than disulfide scrambling, although cases of the formation of reduction-resistant disulfide bonds through disulfide scrambling have been reported. 20 It is notable that previous studies have identified similar types of nonreducible crosslinks for mAbs incubated at similar conditions as those used in our study for promoting deamidation, namely elevated temperature (e.g., 37 C-45 C) and high pH (pH 8-10). 40,[57][58][59][60] Moreover, the observed degree of crosslink formation was significantly different for different antibodies, 57 as we observed in our study.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…The fact that these crosslinks (which primarily form for mAb 1) are nonreducible suggests mechanisms other than disulfide scrambling, although cases of the formation of reduction-resistant disulfide bonds through disulfide scrambling have been reported. 20 It is notable that previous studies have identified similar types of nonreducible crosslinks for mAbs incubated at similar conditions as those used in our study for promoting deamidation, namely elevated temperature (e.g., 37 C-45 C) and high pH (pH 8-10). 40,[57][58][59][60] Moreover, the observed degree of crosslink formation was significantly different for different antibodies, 57 as we observed in our study.…”
Section: Discussionsupporting
confidence: 64%
“…It is also notable that previous studies of photo-oxidation of antibodies found that disulfide bond shuffling can occur via oxidation of Trp residues located in close proximity to intramolecular disulfide bonds through electron transfer or singlet oxygen pathways, and such disulfide scrambling also promotes antibody aggregation. 20,21,48 However, whether similar or unique mechanisms mediate disulfide scrambling for chemical oxidation and photo-oxidation of antibodies is unclear and requires more detailed studies in the future. It is also important to consider that the aggregation behavior of mAbs is strongly influenced by the type of stress and the specific formulation conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7]9 The hypothesis has been used more recently to explain disulfide bond scrambling (formation of non-native disulfide bonds) by reoxidation of photogenerated thiols in human growth hormone and IgG1 antibody. 10,11 UV light has been used to excite solution mixtures of acetone and alcohol to activate radical chemistry that cleaves disulfide bonds into reduced and alkylated sulfur atoms in specific ratios depending on the alcohol. 12 In the gas phase, ultraviolet photodissociation (UVPD) of the covalent bonds in peptides and proteins can be used as a fragmentation method in tandem mass spectrometry.…”
Section: ■ Introductionmentioning
confidence: 99%